Humanatirian aid Storage: a way quick response for victim's ease before and after the disaste - Jasmani, Ismail; Abdul Rahman, Julaila; Rani, Abdul Hakim (2015)
Global warming nowadays are becoming more hostile as it is a catalyst for the current disasters towards the population. The worrying part is the aftermath of the disaster, with a large number of victims suffering of lack of resources such as food and shelter. Although the government and non-government organization (NGOs) are distributing the resources especially the food ration, they have the problems such as inefficient of distributing the ration to the victim places, transportation and packaging design. The victim places sometimes cannot be reached due to poor transportation, lack of man power and poor storage or packaging of humanitarian aid. Therefore, this research proposes the humanitarian aid storage condition that consider the period of time and effect towards the physical properties. This humanitarian aid will contribute the basic supply or resource such as food, medicine and other basic item for daily use at least for 3 days aftermath. The humanitarian aid storage will has the practical condition, its period of time and effect of the ration such as the durability, stiffness, its possible duration of usage need to be tested through its physical properties. Interview, questionnaire and observation will be done to get the detail information. The respondents will be in a few level of ages in several areas so that more accurate data will be collected especially on the way to distribute and handling the storage. To study the storage period of time and effect towards the physical properties, several tests should be made. Through this observation, the storage condition and period of time will influence and effect the physical properties of humanitarian aid goods to ensure it is suitable for the comfortably and usefulness of the victims.